PORTFOLIO OPTIMIZATION OF ESG STOCKS USING THE MARKOWITZ MODEL ON ALL GREEN INDEXES IN INDONESIA - Astri Budiarti; Oktofa Yudha Sudrajad (Journal of Social and Economics Research, 2024)
ESG (Environmental, Social, and Governance) investments are becoming popular because they may provide competitive financial returns while promoting sustainable development. However, the uptake of ESG investments is limited due to barriers such as a lack of understanding and insufficient information. Indonesia has ESG-oriented indexes, such as SRI-KEHATI, ESG Leaders, ESG Sector Leaders IDX KEHATI, and ESG Quality 45 IDX KEHATI serve as a basis for ESG stock selection. This research uses the Markowitz model to optimize an ESG portfolio from four Indonesian green indices. The Markowitz model is employed to determine the optimal weights for establishing a portfolio on the efficient frontier. Using monthly adjusted closing prices from 2019 to 2024, the optimal portfolio suggested by four green indexes offers a balance of risk/return ratio. The optimal portfolio's performance comparison, which is measured by using the Treynor measure, Sharpe ratio, and Jensen's alpha is done to indicate which portfolio provides better risk-adjusted returns. The findings may provide optimal ESG portfolio choices to investor depending on their financial goals and risk tolerance. This research may also inspire other investors who have not yet invested in ESG companies to consider green investing, as ESG stocks provide investors with many benefits.